La selección de alternativas asimétricamente dominadas: Una réplica del efecto de atracción en un contexto culturalmente diferente (The choice of asymmetrically dominated alternatives: A replication of the attraction effect in a culturally different context) - Felix, Reto; Ginocchio, María del Carmen (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract. Decision conflicts in consumer decision making occur when product attributes are negatively correlated and consumers perceive the alternatives as having different advantages and disadvantages. Consumers may resort to some kind of avoidance choice behavior in order to attenuate the negative emotions frequently connected with such conflicts. In this research, the attraction effect is tested in the Northern part of Mexico. The results show that despite cultural differences between Mexico and the United States, the attraction effect occurred in a sample of educated, younger university students in Mexico. However, whereas the attraction effect occurred in a setting based on product choices, it did not occur in a setting based on point-distributions. These findings are discussed in the context of previous research on avoidance choice, and possible explanations for the findings are suggested.